1971
DOI: 10.1042/bj1250285
|View full text |Cite
|
Sign up to set email alerts
|

A reconstituted cell-free system for the specific transfer of steroid–receptor complexes into nuclear chromatin isolated from rat ventral prostate gland

Abstract: 1. A system has been developed for the specific transfer of [(3)H]dihydrotestosterone-receptor complexes into prostatic chromatin in vitro. 2. Under optimum conditions the overall transfer of [(3)H]dihydrotestosterone into purified chromatin in this reconstituted system is entirely consistent with the results obtained in whole tissue both in vivo and in vitro. 3. The transfer of [(3)H]dihydrotestosterone into chromatin is tissue-specific and maximal into chromatin isolated from androgen-dependent tissues. 4. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
53
0
1

Year Published

1976
1976
2009
2009

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 178 publications
(61 citation statements)
references
References 38 publications
7
53
0
1
Order By: Relevance
“…1). This confirms the results of other investigators (15,16 (7,20). The Both these components (A and B) exhibited high affinity and specificity for progesterone, and both associated with isolated chick oviduct nuclei.…”
Section: Resultssupporting
confidence: 81%
See 2 more Smart Citations
“…1). This confirms the results of other investigators (15,16 (7,20). The Both these components (A and B) exhibited high affinity and specificity for progesterone, and both associated with isolated chick oviduct nuclei.…”
Section: Resultssupporting
confidence: 81%
“…The active fraction was freed from unbound hormone by gel -filtration on a Sephadex G-25 column (1 X 24 cm). Sucrose density gradient analysis of the purified [3H]DHT-receptor complex showed that essentially all the radioactivity was associated with the receptor protein peak sedimenting at approximately 8 S. This is in agreement with the reports from other laboratories (15,16). In our system, we were able to detect only a small amount of 3.5S receptor complex, probably because of the (NH4)2SO4 fractionation of the initial extract (16 Samples (1 ml of reconstituted chromatin with [3H]DHTreceptor complex) were analyzed by density gradient centrifugation.…”
supporting
confidence: 82%
See 1 more Smart Citation
“…unloading). However, there is no evidence to support this hypothesis; rather, it has been demonstrated (Mainwaring & Peterken, 1971;Rennie & Bruchovsky, 1973; that administration of androgen results in a net increase in the concentration of androgen receptors in the nucleus that is stoicheiometrically equivalent to a net decrease of androgen receptors in the cytoplasm. Although the second hypothesis cannot be completely discounted, two points argue against its acceptance: first, preparation of nuclei in the presence of a proteinase inhibitor alters the intranuclear distribution of specific dihydrotestosterone-binding sites but not their recovery (20600 sites per nucleus; Barrack & Coffey, 1980); secondly, even with very high reported estimates for nuclear androgen receptors (26000 sites per nucleus) the ratio of total nuclear dihydrotestosterone to receptor is too high (5: 1) to be due to recovery alone (Bruchovsky et al, 1980).…”
Section: Effects Of Dose On the Intracellular Concentration Of Dihydrmentioning
confidence: 90%
“…It was shown that dihydrotestosteronecytosol receptor complex was translocated into nuclei where the complex interacted with chromatin in the rat prostate (Mainwaring and Peterken, 1971;Doorn et al, 1976 ;Davies et al, 1976). In nuclei of the rat prostate a limited part seems to be responsible for binding with the hormonereceptor complex (Mainwaring et al, 1976a, b).…”
Section: Discussionmentioning
confidence: 99%